CAR T-cell therapy for pleural mesothelioma: Rationale, preclinical development, and clinical trials. (July 2021) - Chintala, Navin K.; Restle, David; Quach, Hue; Saini, Jasmeen; Bellis, Rebecca; Offin, Michael; Beattie, Jason; Adusumilli, Prasad S.
Highlights: Tumor antigen-targeted CAR T-cell therapy is effective for leukemia and lymphoma. CAR T-cell therapy is in phase I/II clinical trials for pleural mesothelioma. Regional delivery of CAR T cells achieve systemic immunity. Combination of CAR T cells and anti-PD1 strategies is under investigation. Abstract: The aim of adoptive T-cell therapy is to promote tumor-infiltrating immune cells following the transfer of either tumor-harvested or genetically engineered T lymphocytes. A new chapter in adoptive T-cell therapy began with the success of chimeric antigen receptor (CAR) T-cell therapy. T cells harvested from peripheral blood are transduced with genetically engineered CARs that render the ability to recognize cancer cell-surface antigen and lyse cancer cells. The successes in CAR T-cell therapy for B-cell leukemia and lymphoma have led to efforts to expand this therapy to solid tumors. Herein, we discuss the rationale behind the preclinical development and clinical trials of T-cell therapies in patients with malignant pleural mesothelioma. Furthermore, we highlight the ongoing investigation of combination immunotherapy strategies to synergistically potentiate endogenous as well as adoptively transferred immunity.